The hallowed ones - Bickle, Laura (Graphia, 2012)
Amish teen Katie smuggles a gravely injured young man, an outsider, into her family's barn despite the elders' ruling that no one can come in or out of the community while some mysterious and massive unrest is wreaking havoc in the "English" world.